1994
DOI: 10.1021/bi00188a030
|View full text |Cite
|
Sign up to set email alerts
|

Unique Epitope of Apolipoprotein A-I Expressed in Pre-.beta.-1 High-Density Lipoprotein and Its Role in the Catalyzed Efflux of Cellular Cholesterol

Abstract: The ability of mouse anti-apolipoprotein A-I (apo A-I) monoclonal antibodies to recognize pre-beta-HDL species in native plasma was determined. An antibody identifying residues 137-144 of the mature protein uniquely recognized pre-beta-1 HDL, an HDL species of low molecular weight implicated in early cholesterol transport from cell membranes to plasma [Castro, G. R., & Fielding, C. J. (1988) Biochemistry 27, 25-29]. Incubation of plasma with this antibody significantly inhibited the efflux of labeled cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
52
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 28 publications
8
52
0
Order By: Relevance
“…Several groups have suggested that specific amino acid sequences participate in HDL-mediated cholesterol efflux [4,5,43,44]. In addition it has been suggested that the presence of amphipathic α-helices with high lipid-binding affinity determines the ability of apoproteins to participate in the membrane microsolubilization of cellular phospholipids and cholesterol [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several groups have suggested that specific amino acid sequences participate in HDL-mediated cholesterol efflux [4,5,43,44]. In addition it has been suggested that the presence of amphipathic α-helices with high lipid-binding affinity determines the ability of apoproteins to participate in the membrane microsolubilization of cellular phospholipids and cholesterol [45].…”
Section: Discussionmentioning
confidence: 99%
“…We now have evidence that the modification of DPPC-associated apo A-I by HOCl results in impaired cholesterol efflux from J774 macrophages even at low modification rates [46] with no detectable formation of cross-linked, highmolecular-mass apo A-I. This could result from the modification of T9, T11, T16 and T22, peptides overlapping with specific amino acid sequences contributing to cellular cholesterol efflux [4,5,43,44]. The initial efflux of cellular unesterified cholesterol to HDL occurs by one of two independent mechanisms [47,48], depending on the degree of apo A-I lipidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 The best characterized of the lipid-poor forms of apoA-I is pre-␤1 HDL, a small particle containing only apoA-I and some phospholipid. 1, 46 Fielding et al 6 have reported that apoA-I residues 137 to 144 are adjacent to or part of a structural site in pre-␤1 HDL that is active in promoting the efflux of cellular cholesterol. Another study has attempted to demonstrate that monoclonal antibodies specific to apoA-I residues 140 to 150 are able to inhibit cellular cholesterol efflux from intracellular or plasma membrane pools of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth exon contains homologous sequences that code for ten 11-or 22-amino acid repeats to form amphipathic helixes that mediate biological functions. 5 However, the domains of apoA-I necessary to form distinct HDL subclasses, 6 activate LCAT, 7 bind to cellsurface receptors, 8 and promote cholesterol efflux from cells 9 are not clearly understood. Monoclonal antibodies with epitopes recognizing discontinuous groups of amino acids in residues 143 to 164 were demonstrated to inhibit LCAT activation and cellular cholesterol efflux.…”
mentioning
confidence: 99%